Prospect on Application of Deep-Sea Engineering Technology in Deep-Space Exploration - Hao Zhang; Haoliang Ba; Cong Ye; Hao Wang; Yongchun Shen; Guorui Li; Yanqing Li (中国工程科学)
With the further development of deep-space, deep-sea, and deep-ground technologies, numerous technical connections are found existing between deep-sea engineering and deep-space exploration and thus it is feasible to apply deep-sea engineering technologies to deep-space exploration. By comparing the environmental characteristics of deep space and deep sea, this study reveals the similarities between deep-sea engineering and deep-space exploration in terms of pressure and temperature adaptability. Then, it explores the prospects on structural safety, complex operation technology and equipment, unmanned intelligence and miniaturization of loads, and construction of test sites. It is found that the physical characteristics of the extraterrestrial space is prominently diversified, and the environment of some hotspot planets is similar to that of the deep sea in terms of pressure and corrosion. Therefore, the structure design and anticorrosion technologies regarding deep-sea engineering can be applied to deep-space exploration. Meanwhile, the requirements for complex control and unmanned automation of deep-space exploration equipment are consistent with those of deep-sea engineering equipment; therefore, the research and development of specific equipment from these two fields are interchangeable. The submarine volcanic areas and the Antarctic subglacial lake (i.e., Lake Vostok) have obvious extraterrestrial space characteristics and can be established as test sites for deep-space exploration, which can be regarded as a research direction for deep-sea test sites and new test technologies for deep-space exploration. To sum up, technology exchange and cross-domain application between the deep-sea and deep-space technologies are highly possible, and the full application of deep-sea engineering technologies to deep-space exploration will help China’s deep-space exploration equipment develop faster.